Supporting Conceptual Comprehension of Newton’s Laws of Motion of Grade 8 Students through Kotobee Interactive E-Module - John Jeri A Baring; Julie Santiago Berame (Universitas Muhammadiyah Surakarta, 2022)
This study aimed to develop an interactive electronic module to support students’ conceptual comprehension in Science 8 and find out if there would be a significant difference in the performance of students after using the electronic module. The e-module was composed of three topics with three sub-lessons in Newton’s Laws of Motion. The participants were Grade 8 students and enrolled in the school year 2020-2021. Students from four different sections were divided into two groups: the controlled group (printed module) and the experimental group (e-module). The e-module was validated by nine experts for its content validation. Re-sults showed that the pretest scores of the students in both the controlled and experimental groups had a remark of average mastery. The post-test mean scores showed a large difference between the two groups as the students using printed modules remained at average mastery level while students taking the e-module were moving toward mastery. T-test results also found that the pretest scores of the students using both methods of instruction were statistically significantly different from their post-test scores. The e-modules group had improved and increased gain scores in their posttest compared to the printed modules group. Still, both modules, whether printed or e-modules, contribute to the increased performance of the students. Moreover, the developed interactive e-module using Kotobee Author software met the criteria set for evalua-ting its validity in terms of material worthiness, media feasibility, and language eligibility in supporting students' conceptual comprehension of Newton’s Laws of Motion. Overall, the value of the study was to search for the most effective ways of applying e-learning module in the learning process. Also, the study employed the effectiveness of using the e-module in the development of science teaching and by providing alternative ways to properly utilize the use of e-module in addressing and solving issues and problems in the teaching and learning process. The study would help improve the science curriculum with technology integration to be employed by teachers in the school environment.